Time: a brief reflection on a beautiful invention of the human being (Mayéutica Revista Científica de Humanidades y Artes, 2022)
Perhaps time is one of the existential notions that human beings have tried to understand the most. Although tangible and manifest, it seems to reside in the realm of the ungraspable in immanence . Time cannot be estimated as a physical magnitude. On the contrary, it is closer to a creation or invention. A poetic ideation that occurs in relativity.
Keywords: time; creation; ideation; apperception; movement